2017
DOI: 10.18632/genesandcancer.142
|View full text |Cite
|
Sign up to set email alerts
|

EGFR as a prognostic biomarker and therapeutic target in ovarian cancer: evaluation of patient cohort and literature review

Abstract: BackgroundLimited effectiveness of therapeutic agents targeting epidermal growth factor receptor (EGFR) in clinical trials using unselected ovarian cancer patients has prompted efforts to more effectively stratify patients who might best benefit from these therapies. A series of studies that have evaluated immunohistochemical (IHC) staining of EGFR in ovarian cancer biopsies has produced unclear results as to the utility of this measure as a prognostic biomarker. Here, we used one of the largest, single instit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 67 publications
1
46
0
1
Order By: Relevance
“…3 A). Furthermore, we found FBXL20 outperformed other potential OvCa prognostic molecular markers, including mutation status of BRAC1/2 [ 19 ] and TP53 [ 20 ], and expression levels of WTAP (Wilms' tumor 1-associating protein) [ 21 ] and EGFR [ 22 ] (Supplementary 4). We also found that FBXL20 expression levels and cellular protein levels do not correlate with OvCa staging, indicating FBXL20 can be an independent OvCa prognostic biomarker (Supplementary 5).…”
Section: Resultsmentioning
confidence: 99%
“…3 A). Furthermore, we found FBXL20 outperformed other potential OvCa prognostic molecular markers, including mutation status of BRAC1/2 [ 19 ] and TP53 [ 20 ], and expression levels of WTAP (Wilms' tumor 1-associating protein) [ 21 ] and EGFR [ 22 ] (Supplementary 4). We also found that FBXL20 expression levels and cellular protein levels do not correlate with OvCa staging, indicating FBXL20 can be an independent OvCa prognostic biomarker (Supplementary 5).…”
Section: Resultsmentioning
confidence: 99%
“…However, there is still some conflicting reports. For example, some data favored EGFR as a reliable marker of survival or responsiveness to therapy [ 18 , 19 ] but others did not [ 20 , 21 ], and some reports indicated that using EGFR inhibitors in ovarian cancer patient had not shown favorable clinical outcomes [ 15 , 22 , 23 ]. Thus, in this paper, it was investigated whether CHAG inhibited the development of ovarian cancer cells via abrogation of activation of EGFR and EGF/EGFR mediated signaling cascades.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies examined the expression level of the individual member of the HER family in patients with ovarian cancer. The expression of EGFR, HER-2, HER-3 and HER-4 reported in the literature for ovarian cancer exhibits wide variation ranging from 9–90%, 6.4–52%, 16–69%, and 65–90% of the cases examined respectively, with EGFRvIII expression being rare [ 52 59 ]. In this study of 60 FIGO stage III and IV patients, the expression levels of the EGFR and HER-2 were determined by immunohistochemistry using mAb EGFR.113 and mAb 3B5 respectively.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Mehner and colleagues reported the result of immunohistochemical staining of EGFR in tissue microarrays from 488 ovarian cancer patients. They found while 90% of their tumor specimens had some EGFR staining and 53% had membranous staining, the EGFR staining alone was not of prognostic value [ 59 ]. Also, there is currently conflicting data on the prognostic significance of CD44 in patients with ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%